Modern tragedy : a critical analysis of the elements of tragedy with special reference to N.A. Milubi's plays - Ramukosi, Patrick Mbulaheni (University of Limpopo, 1999)
Refer to document
Thesis (M. A. (African Languages)) -- University of Limpopo, 1999
Keywords: Tragedy; Drama; Tragedy; Drama - History and Criticism; Tshivenda drama (Tragedy)